Investigating English College Students’ Perspectives on National Education Program Kampus Mengajar - Syifa Fuadiyah Rinadi; Yudi Basuki (STKIP PGRI Trenggalek, 2023)
Kampus Mengajar is a program that offers college students the opportunity to engage in off-campus learning for a duration of one semester. As part of this program, students become teaching partners, contributing to innovative and creative strategies and models in targeted educational units. The primary focus is on enhancing students' literacy and numeracy skills within the designated schools. The research's objective was to uncover and describe the perspectives of English college students who participated in the Kampus Mengajar program. Employing a qualitative research approach, the study centered around phenomenological studies. Data analysis was conducted using the triangulation theory and the likert scale. The study's subject pool consisted of 20 English college students enrolled in the Kampus Mengajar program. Validation of the research instrument was achieved through Pearson Correlation and Cronbach's Alpha. Research findings underscored that English college students attending elementary schools expressed strong agreement with the Kampus Mengajar program. Similarly, participants from the junior high school level also conveyed their agreement with the program. Moreover, the study identified several issues faced by English college students upon joining the national Kampus Mengajar program